SMART CITIES AND THE EUROPEAN VISION - Carmen Florina Fagadar (University of Oradea, 2021)
Cities are one of the main factors influencing the economic development and prosperity of societies. Smart cities, fueled by innovation and the Internet of Things, are built on three pillars - improving the residents’ quality of life, business competitiveness, and ensuring a sustainable environment. When applied within the six urban areas: economy, mobility, security, education, living conditions, and environment, cities can much faster make the transition to smart cities. The term smart city is often associated with the desire for accelerated modernization of various spatial and urban social interactions, the term “smart city” often being fuelled by technological developments. Proof of this are the terms used to define the same concept: “digital city”, “e-communities”, “intelligent city”, “e-City”, “wired city”. However, a smart city is called upon to respond to the needs of cities and societies alike to approach challenges in a novel and creative manner. The motivations for transforming existing cities into smart ones are obvious and straightforward. They come on one hand, from the threats of current demographic phenomena (population growth, migration, public health, safety, and living conditions), and also from the opportunities of solutions that can be brought by technological developments and innovation, transformations of generations (new “Digital” generations), and civic involvement (participation and inclusion) in the management of modern cities. Thus, the meaning associated to the name of the smart city does not only overlap with the idea of modernization and expansion, but also wants to combine, simultaneously, competitiveness and sustainable urban development. In the present study, by building upon a European vision as regards the development of smart cities, we have attempted to build an image of the European envisioned smart city, which is to be planned out and sought after through a series of strategic partnerships for innovation. Not only is the European vision detailed, but Romanian specific urban development and smart city tendencies shall also be briefly analyzed in this paper.